LENGTH-WEIGHT RELATIONSHIP AND CONDITION FACTOR OF REEVE’S CROAKER CHRYSOCHIR AUREA (RICHARDSON, 1846) OFF WEST BENGAL COAST - SUSMITA; SRINIVASAN, NAGESH T.; BHAKTA, DIBAKAR; BEHERA, SAMARENDRA; MONDAL, ANWESHA; BODA , S. (Journal of the Inland Fisheries Society of India, 2026)
In the present study, length-weight relationships of Chrysochir aurea have been estimated off the coast of West Bengal. The length of the individual fish ranged from 124 to 417 mm, and the weight ranged from 15.06 to 958.37 g. The LWRs were done for a total of 618 individuals, comprising 286 males, whose sizes ranged from 124-376 mm and 15.06-604.84 g, and 332 females, whose sizes ranged from 131-417 mm and 21.17-958.37 g, collected from trawl catch from September 2021-August 2022. There was no significant variation (p<0.05) in the growth rate between the sexes. The b values were calculated as 3.2714, 3.2725, and 3.2756 for males, females, and pooled sexes, respectively, indicating positive allometric growth patterns. The monthly mean relative condition factor (Kn) varied from 1.00±0.05 to 1.20±0.13 for males and 0.98±0.09 to 1.05±0.32 for females, respectively.